NATURAL EXPOSURE TO ARSENIC-INDUCED GENOTOXIC EFFECTS IN DIABETIC AND NON-DIABETIC INDIVIDUALS - MAHMOOD , S; HUSSAIN , Y; LATIF , I; MAHMOOD , R; IRSHAD , F; ISLAM, EU; MAQSOOD , H (Biological and Clinical Sciences Research Journal, 2024)
Arsenic contamination in drinking water is a global health issue linked to various adverse health outcomes, including genotoxic effects. Understanding these effects in different populations, including diabetic and non-diabetic individuals, is critical for developing targeted public health interventions. Objective: This study aimed to investigate the genotoxic effects of arsenic exposure in diabetic and non-diabetic individuals residing in arsenic-contaminated and control areas. Methods: In this cross-sectional study conducted from January to June 2024, 100 participants were recruited from areas with known differences in arsenic water contamination levels. Participants were divided equally between arsenic-contaminated and non-contaminated regions, with 15 diabetic and 20 non-diabetic individuals selected from each group. A standard questionnaire was administered to collect demographic data and medical history. Additionally, 12 water samples from the contaminated area were analyzed for arsenic concentration. Genotoxic effects were assessed using the comet assay, and DNA damage was quantified using an empirical numerical rating system. Results: Significant DNA damage was observed in the blood cells of individuals from the arsenic-contaminated area compared to those from the non-contaminated area. Diabetic individuals showed similar patterns of DNA damage to non-diabetics within the same exposure group. Even in the non-contaminated group, slight DNA damage was detected, suggesting potential contributions from other environmental factors. Conclusion: The findings demonstrate that arsenic exposure is associated with significant genotoxic effects in both diabetic and non-diabetic populations. DNA damage in non-contaminated areas also indicates a possible impact of other environmental factors. These results highlight the need for ongoing monitoring and mitigation strategies to address arsenic contamination and its health impacts.